Forest and other land cover assessment in Nepal using Collect Earth - Khadka, A.; Dhungana, M.; Khanal, S.; Kharal, D. K. (Banko Janakari, 2020)
Periodic monitoring of land cover is essential to examine the total extent and changes over time. Information derived from forest and other land cover analysis provides key input for policy formulation and management decisions. Land cover patterns on the Earth are constantly being changed by different human activities, thereby influencing biophysical processes. Analysis and mapping of land cover are important aspects in management, planning and monitoring of forest resources. Thus, we designed this study to assess national-level forest and land cover using the Openforis Collect Earth and compare the results with other assessments. We generated a number of systematic sampling points across the country and visually interpreted each of them on this Platform to assess the land cover type. Furthermore, we adopted six land cover classes as prescribed by the IPCC Good Practice Guidance. Our study provided the current status of forest and other different land cover classes. Forest occupied 6.54 million ha (44.47%) followed by Other land 4.22 million ha (28.68%) of the total area of Nepal, respectively. Besides, Cropland, Settlement, Wetland and Grassland covered 3.22 million ha, 0.17 million ha, 0.18 million ha and 0.38 million ha, respectively. The overall accuracy of the interpretation of all the land cover classes was found to be more than 98%. Comparing the results with the past studies, the calculated results of Forest, Cropland, Settlement and Wetland were found to be reliable for reporting purpose. However, further studies are necessary to generate more reliable results in terms of the Other land and Grassland.